Protein mobilization in merminating mung bean seeds involves vacuolar sorting receptors and multivesicular bodies - Wang, Junqi; Hillmer, Stefan; Robinson, David G. (Plant physiology, 2007)
Plants accumulate and store proteins in protein storage vacuoles (PSVs) during seed development and maturation. Upon seed germination, these storage proteins are mobilized to provide nutrients for seedling growth. However, little is known about the molecular mechanisms of protein degradation during seed germination. Here we test the hypothesis that vacuolar sorting receptor (VSR) proteins play a role in mediating protein degradation in germinating seeds. We demonstrate that both VSR proteins and hydrolytic enzymes are synthesized de novo during mung bean (Vigna radiata) seed germination. Immunogold electron microscopy with VSR antibodies demonstrate that VSRs mainly locate to the peripheral membrane of multivesicular bodies (MVBs), presumably as recycling receptors in day 1 germinating seeds, but become internalized to the MVB lumen, presumably for degradation at day 3 germination. Chemical cross-linking and immunoprecipitation with VSR antibodies have identified the cysteine protease aleurain as a specific VSR-interacting protein in germinating seeds. Further confocal immunofluorescence and immunogold electron microscopy studies demonstrate that VSR and aleurain colocalize to MVBs as well as PSVs in germinating seeds. Thus, MVBs in germinating seeds exercise dual functions: as a storage compartment for proteases that are physically separated from PSVs in the mature seed and as an intermediate compartment for VSR-mediated delivery of proteases from the Golgi apparatus to the PSV for protein degradation during seed germination.